Modeling of Control System on Sorting Palm Fruit Machine by Using Arduino Microcontroller - Arief, Dodi Sofyan; Fitra, Edy; Minarni, Minarni; Herman, Herman; Salambue, Roni (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
One of the reasons for the poor quality of palm oil in Indonesia is because of the separation system of processing method is processed manually. In this research, the proposed solution to overcome the problem is by applying the automatic separation system by using microcontroller. The maturity of the fruit will be determined from the image that taken by a camera. The reading of the camera image will be processed in a microcontroller which will move the separator arms so that the fruit will be separated based on the level of maturity. This system is designed to work continuously by placing the palm fruit over a conveyor belt mechanism. With this automation method, the separation process of fruit is no longer depends on the ability of humans manually and more importantly it can take place continuously.